Chronic obstructive Eustachian tube dysfunction: CT assessment with Valsalva maneuver and ETS-7 score - Angeletti, Diletta (PLoS One, 2021)
Chronic obstructive Eustachian tube dysfunction (ETD) is a common disorder of the middle ear. In recent years, two main diagnostic tools have become available: Eustachian tube score (ETS-7) and computed tomography (CT) combined with Valsalva maneuver. The aim of this study is to evaluate the outcomes of ETS-7 and CT in a group of patients affected by middle ear atelectasis with a strong suspicion of ETD. Three males and nine females, affected by middle ear atelectasis with retraction of the TM were enrolled. Each patient underwent to Eustachian tube dysfunction evaluation adopting the ETS-7 score and a temporal bone CT with Valsalva maneuver. The ears analyzed at steady state were divided into 2 groups: ETS<7 group and ETS≥ 7 group. The same division was applied for the ears analyzed after the Valsalva maneuver: ETS<7 group and ETS≥ 7 group. ETs were categorized as “well defined” (WD) and “not defined” (ND). The results of the analysis of the ETS-7 score in all 24 ears showed that 42% presented ETS ≥7, while 58% had ETS <7, indicating a diagnosis of ETD. In the ETS<7 group after Valsalva, ET was visualized in 33% of patients. In the ETS≥7 group it was WD in 29% after the Valsalva manoeuver. In both groups the comparison between the visualization of the ET before and after the Valsalva manoeuver did not present a statistical difference. No correlation emerged between ET evaluation with CT scan during Valsalva maneuver and ETS-7 score. It confirms that there is not a gold standard for the study of ET dysfunction.